2009
DOI: 10.1001/archoto.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Thyroid in Patients With Hearing Loss and Enlarged Vestibular Aqueducts

Abstract: Objective To evaluate thyroid structure and function in patients with enlargement of the vestibular aqueduct (EVA) and sensorineural hearing loss. Design Prospective cohort survey. Setting National Institutes of Health Clinical Center, a federal biomedical research facility. Patients The study population comprised 80 individuals, aged 1.5 to 59 years, ascertained on the basis of EVA and sensorineural hearing loss. Main Outcome Measures Associations among the number of mutant alleles of SLC26A4; volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…Our results differ from other studies that suggested a strong association between two mutant alleles and PS, defined as the identification of a positive PDT and/or goiter (24,45). However, we studied a larger number of patients with two SLC26A4 mutant alleles, namely 21 patients versus 14 in each of the two previous studies, and we performed a greater number of PDT among those patients, namely 17 patients in our study versus 7 (24) and 9 patients (45) in the two previous studies.…”
Section: Evaluation Of Patients With Pendred Syndrome and Evacontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ from other studies that suggested a strong association between two mutant alleles and PS, defined as the identification of a positive PDT and/or goiter (24,45). However, we studied a larger number of patients with two SLC26A4 mutant alleles, namely 21 patients versus 14 in each of the two previous studies, and we performed a greater number of PDT among those patients, namely 17 patients in our study versus 7 (24) and 9 patients (45) in the two previous studies.…”
Section: Evaluation Of Patients With Pendred Syndrome and Evacontrasting
confidence: 99%
“…This recruitment mode is original and permitted us to examine a wider panel of affected patients, but it introduced a recruitment bias and prevented us from performing statistical analysis in the overall population. Another significant difference with these two previous studies (24,45) is that they were performed in the United States where iodine intake is higher than in France.…”
Section: Evaluation Of Patients With Pendred Syndrome and Evamentioning
confidence: 80%
“…The perchlorate discharge phenotype-genotype correlation was dependent upon uniform test procedures and interpretation, and comprehensive screening to exclude patients with other confounding phenotypic abnormalities [35]. Madeo et al [47] used ultrasonography to calculate thyroid gland volume and defined goiter by comparison to published normative data. Thyroid gland enlargement was primarily dependent on the presence of two mutant alleles of SLC26A4 in pediatric (<10 years old) EVA patients, but not in older EVA patients [47].…”
Section: Slc26a4 Genotype-phenotype Correlationmentioning
confidence: 99%
“…Madeo et al [47] used ultrasonography to calculate thyroid gland volume and defined goiter by comparison to published normative data. Thyroid gland enlargement was primarily dependent on the presence of two mutant alleles of SLC26A4 in pediatric (<10 years old) EVA patients, but not in older EVA patients [47].…”
Section: Slc26a4 Genotype-phenotype Correlationmentioning
confidence: 99%
“…We also analysed the segregation of EVA and SLC26A4 in families with non-diagnostic SLC26A4 genotypes. Since we have never observed abnormal perchlorate discharge results from EVA patients with non-diagnostic SLC26A4 genotypes,7 18 19 we did not include thyroid phenotype in our analyses. Our results provide insight into the aetiology of EVA and estimates of recurrence risk that will be useful when counselling families.…”
mentioning
confidence: 99%